Digitized imagination - Rajan, Nalini. (ed.) (London, 2009)
The work explores the complex and profound implications of digital technology for a stunning variety of spaces, ranging from science and cinema to citizenship and bazaars. It maps the multiple ways in which the 'new' media rewrites the 'old', and the dilemmas and issues that they pitch - questioning, in turn, received notions of knowledge, legality, ethics, privacy, identity and community. The book argues that the old and the new media are neither radically different nor the same: while the mutability of a narrative, whether on the printed page or on a digitally recorded disk remains, there are intrinsic differences between print and digital print.
Keywords: Digital media